Recursos educativos abiertos para el aprendizaje de la asignatura de lengua y literatura del 7mo año de educación general básica - Apolo Vera, Mary Germania; Brito Sánchez, Pamela Estefanía (Machala, 2022)
The present investigation has been developed in a virtual environment for reasons of a pandemic, which is called COVID-19, which caused many educators and students to receive and exercise their classes through videoconferencing technological tools to continue with our educational process. but virtually. For this reason, the educational institution of Basic Education Dr. Camilos Gallegos Domínguez of the City of Machala in the province of El Oro has been taken into account. Institution where the object of study derived by the students of the seventh year of basic general education of the subject of Language and Literature was chosen, where the use of Open Educational Resources organized in an educational blog with a creative, dynamic interface and design was applied. and innovative for student learning. The research is derived from two approaches the first: qualitative used in experience I with the teacher of the subject of Language and Literature, where information and data could be collected on the possible improvements in the prototype and the level of acceptance that it would have when apply it to students. And the other approach is the quantitative one executed in experience II with the seventh year EGB students through the application of a survey that served us for data collection, analysis, tabulations in tables and graphs and thus obtain a level of acceptance that you have had the prototype in your application. Through the use of OER in education, it has been possible to implement and execute the use of different technological tools to favor academic content, interactive activities and thus motivate their participation, collaboration, dynamism and critical thinking using ICT during their teaching-learning process. For the development of the research, a central problem was sought, which I pose as follows: How does the implementation of Open Educational Resources favor the teaching-learning of Language and Literature in seventh-year EGB students parallel "A" from the basic education school “Dr. Camilo Gallegos Domínguez" located in the City of Machala in the province of El Oro? As a result of this, objectives were also set, a general objective for the research constituted as follows: Implement Open Educational Resources for learning the subject of Language and Literature in seventh-year EGB students parallel "A" of the school of basic education “Dr. Camilo Gallegos Domínguez, located in the City of Machala in the province of El Oro. and a general objective for the prototype constituted as follows: Implement an educational blog, through the "Blogger" platform for the improvement in the teaching-learning process of the subject of Language and Literature in the students of seventh year EGB of the School of basic education Dr. Camilo Gallegos Domínguez, of the city of Machala. In this way, for the creation of the educational blog with the OERs implemented in it, the ADDIE methodology was applied, which through its five phases: analysis, design, development, implementation and evaluation, achieved the assembly of the prototype for the language subject. and literature. Since when using the technological tools for the creation of the OER, a follow-up and search for more techniques to apply them in the classroom was carried out. And as a last moment, the results obtained in experiences I and II are shown, through the data collection instruments of the interview and the survey, with their respective tabulations; charts, tables and general analysis per question.
La investigación presente se la ha desarrollo en un ambiente virtual por motivos de pandemia, la cual esta denominada como COVID-19, la cual hizo que muchos educadores y educandos reciban y ejerzan sus clases mediante herramientas tecnológicas de videoconferencias para seguir con nuestro proceso educativo, pero de manera virtual. Por aquello se ha tomado en cuenta la institución educativa de Educación Básica Dr. Camilos Gallegos Domínguez de la Cuidad de Machala de la provincia de El Oro. Institución en donde se escogió el objeto de estudio derivado por los estudiantes de séptimo año de educación general básica de la asignatura de Lengua y Literatura en donde se aplicaron el uso de Recursos Educativos Abiertos (REA) organizados en un blog educativo con una interfaz y diseño creativo, dinámico e innovador para el aprendizaje de los estudiantes. La investigación esta derivada de dos enfoques el primero: cualitativo empleado en la experiencia I con el docente de la asignatura de Lengua y Literatura, en donde se pudo recolectar información y datos sobre las posibles mejoras en el prototipo y el nivel de aceptación que tendría al aplicarla con los estudiantes. Y el otro enfoque es el cuantitativo ejecutado en la experiencia II con los estudiantes de séptimo año de EGB mediante la aplicación de una encuesta que nos sirvió para la recolección de datos, análisis, tabulaciones en tablas y gráficos y así obtener un nivel de aceptación que ha tenido el prototipo en su aplicación. Mediante el uso de los REA en la educación se ha podido implementar y ejecutar el uso de diferentes herramientas tecnológicas para favorecer los contenidos académicos, actividades interactivas y así motivar su participación, colaboración, dinamismo y pensamiento crítico utilizando las TIC durante su proceso de enseñanza aprendizaje. Para el desarrollo de la investigación se buscó un problema central, el cual se lo planteo de la siguiente manera: ¿Cómo favorece la implementación de Recursos Educativos Abiertos para la enseñanza aprendizaje de Lengua y Literatura en los estudiantes de séptimo año EGB paralelo “A” de la escuela de educación básica “Dr. Camilo Gallegos Domínguez” ubicada en la Cuidad de Machala de la provincia de El Oro? A raíz de esto también se plantaron objetivos, un objetivo general para la investigación constituido de la siguiente manera: Implementar Recursos Educativos Abiertos para el aprendizaje de la asignatura de Lengua y Literatura en los estudiantes de séptimo año EGB paralelo “A” de la escuela de educación básica “Dr. Camilo Gallegos Domínguez, ubicada en la Cuidad de Machala de la provincia de El Oro. y un objetivo general para el prototipo constituido de la siguiente manera: Implementar un Blog educativo, mediante la plataforma “Blogger” para el mejoramiento en el proceso de enseñanza aprendizaje de la asignatura de Lengua y Literatura en los estudiantes de séptimo año EGB de la Escuela de educación básica Dr. Camilo Gallegos Domínguez, de la ciudad de Machala. De esta manera para la creación del blog educativo con los REA implementados en él, se aplicó la metodología ADDIE, la cual mediante sus cinco fases: análisis, diseño, desarrollo, implementación y evaluación se logró cumplir con ensamblaje del prototipo para la asignatura de lengua y literatura. Ya que al usar las herramientas tecnológicas para la creación de los REA se realizó un seguimiento y búsqueda de más técnicas para aplicarlas en el aula de clase. Y como último instante se muestran los resultados obtenidos en las experiencias I y II, mediante los instrumentos de recolección de datos de la entrevista y la encuesta, con sus respectivas tabulaciones; gráficos, tablas y análisis general por pregunta.
Keywords: REA; GAMIFICACION; PARTICIPACION; BLOG EDUCATIVO; ADDIE; HERRAMIENTA TECNOLOGICA